CERT Technologies - Alenezi, Khalid; Alshaikhli, Imad Fakhri Taha; Abdullah, Lili Marziana; AlAhmad, Mohammad A. (IJISM, 2015)
Members of the incident response team should have excellent technical skills, such as system administration, network administration, programming, technical support, malware analysis, and intrusion detection. Moreover, supporting system state and status reporting are associated with enabling automated mechanisms with the hardware or software that report information about the system, including abnormal behavior, intrusion attempts, or any other data that would be useful in detecting an incident, understanding impact, and quickly supporting resolution. In order to effectively protect GE and Non-GE entities from cyber-attacks, multiple layers of defenses strategies are needed to combat multiple security issues. The strategy is based on using appropriate security countermeasures across operational, network, and host functionality of GE and Non- GE entities. Therefore, we proposed four zones segment information architecture for securing the main assets and services of GE and Non-GE entities in Kuwait. In each of these zones specific and unique security focus are addressed. For each zone of the layered cyber-security systems architecture, technological security elements are presented to help in securing IT assets and services of the organizations. Such a layered cyber-security systems architecture will assist the organizations in creating clear boundaries in order to effectively and practically apply multiple layers of defenses.